Persuade - Lares, Andres; Cochran, Jeff; Digan, Shaun (Ascent Audio, 2021)
Transform your ability to persuade and negotiate with this practical new resource In Persuade: The 4-Step Process to Influence People and Decisions, accomplished sales, negotiation, and influence experts Andres Lares, Jeff Cochran, and Shaun Digan, PhD, deliver a concise and insightful take on how to transform your ability to persuade others regardless of the setting. In this important book you'll discover: - Original research and scientific studies shedding light on the human decision-making processes that drive success and failure in virtually all interactions - Real world examples and practical exercises to illustrate and practice the concepts discussed - A fun yet rigorous approach of a complex subject that can be practically applied in any business situation Persuade is perfect for executives, managers, entrepreneurs, and other business leaders and will earn a place in the libraries of any professional who negotiates or influences on a regular basis. It is an invaluable resource for anyone seeking to improve their persuasion or deal-making abilities.